Disruptive fintech the coming wave of innovation in financial services with thought leadership provided by CEOs - Deitch, James (Walter de Gruyter GmbH, 2020)
Throughout history, innovators have disrupted existing financial services norms to change the landscape of the marketplace. Disruptive Fintech briefly traces fractional reserves, the creation of bank currency that traded at a premium to bullion value, central bank regulation, securitization of assets and loans, the current state of digital currency and electronic payments. The author then looks toward the future of fintech and the forces of disruption that will change the landscape of financial life as we know it. Using over 100 interviews with thought leading CEOs, this book develops a methodology to identify financial services that are ripe for innovation and discusses how innovative thinking can be used as a disruptive weapon to attack incumbents and create effective new fintech models. The book discusses How to relate historical innovations and disruptions in financial services to the current landscape How to follow a process to identify the threats facing incumbent processes and businesses, and how innovative thinking can be used as a disruptive weapon to attack incumbents and create effective new fintech models How many fintech innovations will be constructed by re-arranging or re-purposing existing core processes In this insightful book, author James Deitch, CPA CMB, argues that some of today's high-flying fintech innovators will flourish, but many may perish as the fire of innovation consumes those fintechs that are slow to monetize their promises.